DISTRIBUSI DAN POLA PERTUMBUHAN IKAN BULAN-BULAN (Megalops cyprinoides Broussonet, 1782) DI SUNGAI BELAWAN - Khairul, Khairul; Wahyuningsih, Hesti; Jumilawati, Erni (Fakultas Perikanan dan Kelautan Universitas Riau, 2014)
The purpose of the study to determine the distribution and growth patterns ofindo pacific tarpon fish (Megalops cyprinoides Broussonet, 1782) in Belawan River.This study was conducted in January-March 2014. Sampling was collected by purpo-sive sampling method. Sampling colected at 3 stations fishnet use with 30 times thestocking for each month. Distribution is calculated using the formula Khouw (2009)and the growth patterns using formulas King (1995). The results showed the analysisof Indo Pacific tarpon fish distribution uniform categorized months as earned valueid <1. Growth pattern of indo pacific tarpon fish is negative allometric means thelength faster than weight gain.